PERBEDAAN KINERJA KONSELOR DALAM MELAKSANAKAN LAYANAN KONSELING PERORANGAN ANTARA KONSELOR LULUSAN PPK DENGAN KONSELOR YANG BELUM MENEMPUH PPK SE-JAWA TENGAH - Aprilianto, Wahyu Candra (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
The Individual counseling services have to be conducted appropriately to ideal stages and procedures. But in fact, the conducting of individual counseling services by counselors is adverse. This research has special purpose to compare the performance of individual counseling service by counselors who graduated from PPK with counselors who had not taken opportunity in PPK. The population of this research is all counselors in Central of Java who act in junior high school, senior high school and vocational school. The sampling method in this research  is the method of area sampling. The method of collecting research data is anonymous questionnare with closed form. The methods of data analysis are descriptive statistic and t-test.  This research results that the performance of individual counseling service by counselors who graduated from PPK is in high level, whereas the performance of individual counseling service by counselors who had not taken opportunity in PPK is in moderate level. From the t-test,  the researcher  has find the significant difference between the performance of individual counseling service by counselors who graduated from PPK and the performance of individual counseling service by counselors who had not taken opportunity in PPK. The conclusions are the performance of individual counseling service by counselors who graduated from PPK is in high level, whereas the performance of  individual counseling service by counselors who had not taken opportunity in PPK is in moderate level and there is significant difference between the performance of  individual counseling service by counselors who graduated from PPK and the performance of  individual counseling service by counselors who had not taken opportunity in PPK.